Between Rebellion and Statesmanship: Attempting a Biography of Ivanko, 1196/1200 (?) - Dall’Aglio, Francesco (Studia Ceranea, 2021)
The paper analyses the actions of Ivanko, a Bulgarian nobleman, possibly a member of the ruling family of the Asenides, who in 1196 killed the ruling tsar, Asen, and escaped to Constantinople once his plan to take control of the country failed. Owing to the benevolence of Alexios III Angelos, he joined the Byzantine military and very quickly rose through its ranks until he became the military commander of the region of Philippopolis. In 1198 or 1999 he defected and created an independent dominion on the slopes of the Stara Planina massif, precariously balanced between Bulgaria and the empire, exploiting to his own advantage the constant state of warfare between the two polities. His adventure was short-lived: in 1200 he was captured through deception by the Byzantines, taken prisoner, and presumably executed. While his political career was very short, his importance for the history of medieval Bulgaria is not to be underestimated. It is a testimony of the fluidity of the political situation at the Bulgaro-Byzantine border, whose instability often allowed ambitious and cunning local commanders to carve up autonomous dominions, and of the difficulties experienced by the central power in keeping control of the peripheral areas of the state. It is also proof of the constantly shifting ethnic and cultural allegiances of the citizens of those polities, entangled between different and often conflicting identities, usually regarded as irreconcilable but that were actually the object of a continuous negotiation and adjusting. Ivanko is an interesting case study in regard to all of those factors, especially when considered within the larger phenomenon of provincial separatism in the imperial (and Bulgarian) lands between the end of the 12th and the beginning of the 13th century.